Heparin and rosuvastatin calcium-loaded poly(l-lactide-co-caprolactone) nanofiber-covered stent-grafts for aneurysm treatment. (27th July 2017) - Feng, Wenhao; Liu, Peixi; Yin, Haiyue; Gu, Ziqi; Wu, Yu; Zhu, Wei; Liu, Yingjun; Zheng, Hao; MO, Xiumei
Abstract : Heparin and rosuvastatin calcium cause P(LLA-CL) nanofibers to exhibit good cell viability and anticoagulation ability. Abstract : Restenosis caused by thrombopoiesis is one of the biggest hindrances to endovascular stent-grafts. Rapid endothelialization of the lumen of the stent is a promising approach to prevent thrombosis. A stent-graft covered with heparin and rosuvastatin calcium-loaded P(LLA-CL) nanofibers via coaxial electrospinning has been fabricated as a novel type of stent-graft. The morphology and inner-structure of the core–shell nanofibers were respectively observed by scanning electron microscopy and transmission electron microscopy. The mechanical properties, water contact angle, release profile of rosuvastatin calcium, cell adhesion and proliferation, and anticoagulation properties in vitro were investigated. The results showed that heparin and rosuvastatin calcium were successfully encapsulated in the nanofibrous matrix, and it would not rupture with the expansion of the stent-graft, relying on the excellent mechanical properties of the P(LLA-CL) coaxial nanofibers. The core–shell nanofibers exhibited a uniform and smooth morphology. The rosuvastatin calcium loaded within the P(LLA-CL) coaxial nanofibers showed a sustained release profile. Because of the existence of rosuvastatin calcium, HUVECs can grow and proliferate well on these electrospun nanofibers, indicating that this material has good cytocompatibility. Furthermore, the anticoagulation experiment shows that this material has a remarkable anticoagulation ability. This stent-graft will be implanted in a rabbit model to test whether aneurysms can be obliterated after stenting. This work provides a promising approach to fabricate stent-grafts for aneurysm treatment.